2011
DOI: 10.1097/mrr.0b013e32834d2048
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward people with disabilities caused by illness or injury

Abstract: This study examined differences in attitudes toward and reactions to individuals with comparable disabilities caused by injury or illness. Participants were students and healthcare professionals randomly assigned to read one of eight vignettes constructed in a between-subjects, full-factorial design: 2 (illness/injury)× 2 (male/female)× 2 (visible/not visible). Participants completed questionnaires measuring reactions to the target person and attitudes toward people with disabilities. We found that both studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 48 publications
0
29
1
Order By: Relevance
“…Negative forms of ableism have been well documented, and include shaming language (Coombs, Chopra, Schenk, & Yutan, ), gestures of disgust (Kouznetsova, Stevenson, Oaten, & Case, ), avoidance (Shiloh, Heruti, & Berkovitz, ), and outright aggression that manifests as brutality from caregivers, and hate crimes that target people because of their disabilities (Sherry, ). In fact, degradation, humiliation, and hostile punishments are often justified as necessary to defend against those whose human status can be questioned because they fail to walk upright, appear bereft of self‐reflection, drool, or leak urine and feces (Haslam & Loughnan, ).…”
Section: Hostile Ableism Researchmentioning
confidence: 99%
“…Negative forms of ableism have been well documented, and include shaming language (Coombs, Chopra, Schenk, & Yutan, ), gestures of disgust (Kouznetsova, Stevenson, Oaten, & Case, ), avoidance (Shiloh, Heruti, & Berkovitz, ), and outright aggression that manifests as brutality from caregivers, and hate crimes that target people because of their disabilities (Sherry, ). In fact, degradation, humiliation, and hostile punishments are often justified as necessary to defend against those whose human status can be questioned because they fail to walk upright, appear bereft of self‐reflection, drool, or leak urine and feces (Haslam & Loughnan, ).…”
Section: Hostile Ableism Researchmentioning
confidence: 99%
“…have been reported some moderately differences in attitudes toward and reactions to individuals with disabilities caused by injury or illness between male and female students. [15]…”
Section: Discussionmentioning
confidence: 99%
“…[1315] In a community-based school education program for prevention of mushroom poisoning in all grades in children, Malinowska-Cieslik and Van den Borne reported the strongest increase in knowledge in the youngest age group (6-7 years old) and in the oldest age group (10-11 years old). [13]…”
Section: Discussionmentioning
confidence: 99%
“…A total of eight studies examined gender as an in uential factor [10,[18][19][20][21][22][23][24] . Among them, signi cant differences were found in attitude between men and women in six studies [10,[18][19][20][21][22] , while two other studies reported that there is no relationship between gender and attitudes toward people with disabilities [23,24] . Particularly, within these six studies, ve studies found that males view persons with disabilities more negatively than females [18][19][20][21][22] .…”
Section: Demographic Factorsmentioning
confidence: 99%